EKO-INOVASI DALAM PARIWISATA PUSAKA: BAGAIMANA UMKM KULINER LOKAL DI PANGKEP MELESTARIKAN RASA MELALUI RESILIENSI EKO DIGITAL - Agung Muliaman Anas; Damas Gianlugi Alrizqi; Yulnita Muchtar (Universitas Ichsan Sidenreng Rappang, 2026)
The integration of intangible cultural heritage preservation and environmental sustainability presents complex challenges for Micro, Small, and Medium Enterprises (MSMEs) in tourism destinations, particularly within conservation areas such as UNESCO Global Geoparks. This study aims to investigate the dynamics of eco-innovation in the traditional culinary sector of Pangkajene and Kepulauan (Pangkep) Regency, South Sulawesi. Employing a mixed-methods research design combining quantitative surveys and in-depth case studies, this research analyzes three primary heritage commodities: Dange cake, Milkfish (Bandeng) processing, and Sop Saudara. The findings reveal a strong